Hospital presentations with diabetic ketoacidosis: A retrospective review. (March 2023) - James, Steven; Annetts, Kylie; Frakking, Thuy; Broadbent, Marc; Waugh, John; Perry, Lin; Lowe, Julia; Clark, Sean
Abstract: Background: Diabetic ketoacidosis (DKA) is a significant source of preventable episodes of care and cost. This study aimed to describe the demographic and clinical characteristics of people with type 1 diabetes (T1D) presenting to the Emergency Department (ED) with DKA in an area of socio-economic deprivation in metropolitan Queensland, Australia, and to describe factors associated with hospital admission and re-presentation in this population. Methods: This was a retrospective descriptive analysis of routine healthcare record data for January 2015-December 2019. People with T1D were identified through hospital discharge codes. Results: More than half (n = 165) the estimated local T1D population (n = 317) experienced an index ED presentation for DKA; mean±SD age at ED presentation was 31.1 + /− 19.3 years, 126 (76.4%) were aged ≥ 16 years and 20 (12.1%) were newly diagnosed. Index DKA presentation was significantly associated with female sex (p = 0.04) but no other demographic or geographic variables. More than half the presentations (n = 92, 55.8%) occurred outside regular business hours. Twenty-three representations occurred within 90 days, associated with older age (p = 0.045) and lower residential socio-economic score (p = 0.02). Conclusion: Findings highlight the frequent problem of DKA and the importance of socio-economic influences. This flags the need and opportunity to improve support to people with T1D to promote diabetes self-care.